2002
DOI: 10.1191/0267659102pf573oa
|View full text |Cite
|
Sign up to set email alerts
|

Use of autologous blood as part of the perfusate for cardiopulmonary bypass: a priming technique

Abstract: In an attempt to replace the oncotic and protein coating capabilities of serum albumin in the perfusate, we established a priming protocol that used autologous blood as part of the perfusate solution. Prior to March 1, 1999, our standard priming protocol was 1650 ml of crystalloid with 250 ml of 5% serum albumin and 5,000 units of heparin. After removing albumin from our prime, our standard protocol was altered to include 40 ml of the patient's autologous blood in 1,800 ml of crystalloid and 10,000 units of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Eighty patients (50.0%) received either Normosol R ® (Abbott Laboratories, Montreal, PQ, Canada) or Plasmalyte A ® (Baxter, USA) as a crystalloid only prime (mean 1783 ± 154 mL). Fifty-six patients (35.0%) received a combination of 50 mL autologous blood as described by Myers et al (13) and Normosol R (mean 1885 ± 91 mL). Twentyfour patients (15.0%) received a combination of 500 mL Pentaspan ® (Braun Medical, Melsunger, Germany) and Plasmalyte A (mean 1693 ± 226 mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty patients (50.0%) received either Normosol R ® (Abbott Laboratories, Montreal, PQ, Canada) or Plasmalyte A ® (Baxter, USA) as a crystalloid only prime (mean 1783 ± 154 mL). Fifty-six patients (35.0%) received a combination of 50 mL autologous blood as described by Myers et al (13) and Normosol R (mean 1885 ± 91 mL). Twentyfour patients (15.0%) received a combination of 500 mL Pentaspan ® (Braun Medical, Melsunger, Germany) and Plasmalyte A (mean 1693 ± 226 mL).…”
Section: Methodsmentioning
confidence: 99%
“…Over the past several years, clinicians have attempted to use various perfusate combinations to preserve platelet protection (11)(12)(13)(14), and manufacturers have been developing polymers to solve the problem of bio-incompatibility by coating the surfaces of oxygenators and extracorporeal tubing with biopassive materials that prevent fibrinogen and platelets from reacting to their surfaces (15)(16)(17). These surface-modifying additives have taken many forms, such as Carmeda ® and Trillium ® coatings (Medtronic, Inc., Parker, CO), Duraflo II ® (Baxter Healthcare Corp., Deerfield, IL), Surface Modifying Ad-ditive ® (Cobe-Sorin, Arvada, CO), X Coating ® (Terumo Corporation, Tokyo, Japan), and Bioline ® and Safeline ® coatings (Jostra Medizintechnik, Hirrlinger, Germany) (18).…”
mentioning
confidence: 99%
“…Crystalloids, like Ringers and lactated Ringers, lead to an increase in interstitial fluid accumulation [ 21 ]. Colloids, for example, gelofusine or hydroxyethyl starch, increase COP more than crystalloids, and subsequently reduce fluid requirements during CPB [ 22 ]. Previous studies have demonstrated that human albumin and colloids as hydroxyethyl starch prevented an increase in extravascular lung water index compared to crystalloids [ 15 , 17 ].…”
Section: Interventionmentioning
confidence: 99%
“…In contrast, priming with colloids has several advantages. Colloids containing human albumin are associated with increased COP compared to crystalloids, resulting in reduced fluid requirements during cardiac surgery with CPB [ 5 ]. Moreover, human albumin has 2 beneficial properties.…”
Section: Introductionmentioning
confidence: 99%
“…First, it protects the endothelial glycocalyx by preferentially binding to the glycocalyx, generating an endothelial surface layer [ 6 ]. Second, albumin influences haemostasis during cardiac surgery by preserving platelet count [ 5 ]. Despite these potential advantages of human albumin as a priming fluid, its cost and risk of potentially severe anaphylactic reactions limit its use [ 7 ].…”
Section: Introductionmentioning
confidence: 99%